Механізм адміністративно-правового захисту прав дитини в Україні - Коломоєць, Н. В.; Kolomoiets, N. V.; ORCID: http://orcid.org/0000-0003-4623-610X (Приватне та публічне право. - 2018. - № 4. - С. 45–49, 2018)
У статті досліджується сутність терміна «механізм адміністративно-правового захисту прав дитини в Україні» та його складові елементи. Особлива увага приділяється суб'єктам адміністративно-правового захисту прав дитини. Відзначається, що існують ті з них, які реалізують свої повноваження на вітчизняному рівні і ті, які діють на міжнародному рівні. В результаті дослідження були сформовані ознаки і авторське визначення механізму адміністративно-правового захисту прав дитини в Україні.

The article is focused on studying the mechanism of administrative and legal protection of children rights in Ukraine. The urgency of the chosen topic is conditioned by the need to formulate the key concepts in the field of children rights protection. Therefore, as the result of the study, the author has formed own definition of the term of “mechanism of administrative and legal protection of children rights in Ukraine”, which has been suggested to understand as the complex universal system presented by the mutual unity of the subjects of administrative and legal protection of children rights, whose actions are coordinated in a definite area; appropriate means of administrative and legal influence, as well as legal guarantees that ensure the realization and protection of children rights. On the basis of the formed definition, the structural elements of administrative and legal protection of children rights in Ukraine are offered to include: 1. subjects of administrative and legal protection of children rights, who act at the state level or at the level of international community depending on the scope of powers; 2. legal guarantees of administrative and legal protection of children rights that confirm the existence of the rights, freedoms and legitimate interests of children and the possibility of their legal guaranteeing and protection; 3. means of administrative and legal protection of children rights, which promote the realization and protection of children rights, freedoms and legitimate interests. In the course of the study, the author has also formed the features of the mechanism of administrative and legal protection and guaranteeing children rights, which include: arrangement and mutual unity of structural elements; specific certainty and clear orientation of actions of all elements; normative regulation of procedural activity; interaction of all structural elements; balance of competence components of structural elements; availability of measures of administrative influence and public convenience.

В статье исследуется сущность термина «механизм административно-правовой защиты прав ребенка в Украине» и его составляющие элементы. Особое внимание уделяется субъектам административно-правовой защиты прав ребенка. Отмечается, что существуют те из них, которые реализуют свои полномочия на отечественном уровне и те, которые действуют на международном уровне. В результате исследования были сформированы признаки и авторское определение механизма административно-правовой защиты прав ребенка в Украине.
Mechanism of Administrative and Legal Protection of Children Rights in Ukraine
Коломоєць, Н. В. Механізм адміністративно-правового захисту прав дитини в Україні / Коломоєць Н. В. // Приватне та публічне право. - 2018. - № 4. - С. 45–49.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; children rights; administrative and legal protection; subjects of authoritative powers; measures of influence; legal guarantees; права ребенка; права дитини; адміністративно-правовий захист; административно-правовая защита